“I have some wishes, which are actually demands.” A qualitative mixed methods study on the impact of consumerism on the therapeutic relationship in mental healthcare - Krikken Mulders, L. T. E.; Tonkens, E. H.; Trappenburg, M. J. (Frontiers in Health Services, 2024)
IntroductionAlongside the logic of care, many Western welfare states have introduced market elements or a logic of choice in their healthcare systems, which has led to consumerist behavior in patients. For the medical field, it is well documented how consumerism creates complex ethical dilemmas and undermines ways of thinking and acting crucial to healthcare. Little is known about these dynamics in mental healthcare.MethodsThis study used a qualitative mixed methods design, combining 180 online patient narratives (blogs) with 25 interviews with therapists in a grounded theory approach.ResultsFindings show that articulate behavior can be divided into two categories: assertive and adamant. While assertive behavior is understood as an integral, reciprocal part of therapy and is stimulated by therapists, adamant or consumerist behavior is experienced as damaging the relationship—the “commodity” the patient is seeking to obtain, as the single most important predictor of treatment success. Findings also show that articulate behavior in both varieties takes a different shape over time during the course of treatment.DiscussionAdamant behavior clashes with the internal logic of care, which is especially problematic in mental healthcare where the relationship with one's therapist is key to successful treatment. Therefore, patients should be taught and helped to display assertive behavior without resorting to adamancy. Individual therapists cannot achieve this alone; this endeavour should be supported by their organizations, societal beliefs about therapy and policy choices.